A Smoothing SAA Method for a Stochastic Linear Complementarity Problem (Communications in Mathematical Research, 2021)
Utilizing the well-known aggregation technique, we propose a smoothingsample average approximation (SAA) method for a stochastic linear complementarityproblem, where the underlying functions are represented by expectations of stochastic functions. The method is proved to be convergent and the preliminary numericalresults are reported.
Keywords: aggregation technique; smoothing SAA method; stochastic linear complementarity problem.